Efficacy of Semaglutide in Pediatric Patients With Bardet-Biedl Syndrome and Alström Syndrome - Hajar Dauleh (18002500) (2025)
Bardet-Biedl syndrome (BBS) and Alström syndrome (AS) are rare autosomal recessive ciliopathies characterized by severe multisystemic involvement, including metabolic, sensory, and developmental impairments. Both conditions result from primary cilia dysfunction, disrupting pathways such as leptin and insulin signaling, which leads to obesity and insulin resistance. While setmelanotide, a melanocortin-4 receptor agonist, may be an effective therapy for obesity in these conditions (especially BBS), its cost limits accessibility for many patients. We describe two pediatric cases (one with BBS and another with AS) demonstrating significant metabolic improvements with semaglutide, a glucagon-like peptide-1 receptor agonist. These observations suggest that some cases of BBS and AS may be treated with semaglutide. Other Information Published in: JCEM Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1210/jcemcr/luaf266